PENINGKATAN KEMAMPUAN MEMORI ANAK PADA KONSEP ANGKA MELALUI PERMAINAN ULAR TANGGA - Dhita Paranita Ningtyas (AWLADY : Jurnal Pendidikan Anak, 2018)
Calistung's learning is not a difficult lesson for early childhood, but its recognition to children must be in the right way so that children can know and understand well. Researchers do research Improvement of memory on the concept of numbers in children Group A in BKB Mawar Jakarta is aimed to improve the memory capacity of children aged 4-5 years in learning to know the concept of numbers dipembelajaran early school entrance. So when the child understands correctly and in a fun way the child can more quickly remember and stored in the child's memory. This research uses "Action Research" research method with 2 implementation cycles. The results of this study are expected with this modified snake ladder game can improve the child's memory on the concept of numbers so that children can understand well about the basics of mathematics learning.